Out scaling of improved cassava processing technology - Uganda lessons - Okidi, J.; Ntawuruhunga, Pheneas; Mukama, E.; Mutyaba, C.; Agona, A.; Oliveira, F.; Wanda, K. (International Society for Tropical Root Crops, 2012)
Cassava (Manihot esculenta Crantz) has an immediate potential for use in food and feed industry in East and Central Africa (ECA). However, its industrial utilization in the region remains low, partly due to lack of improved processing technologies, lack of awareness of the alternative uses of cassava and technical know how for commercialization. To tap the potential of cassava in feed industry of Uganda, EARRNET and its partners, NARO, Ugachick and farmers, established in 2005 two pilot processing sites in the districts of Bukedea and Masindi. Site selection was based on the levels and potential for increasing cassava production, existence of farmer groups/association, storage facility, availability of reliable clean water supply and ease of access to market. The objectives of the project were to a) increase awareness on the benefits of using high quality cassava chips in feed industry, b) introduce and promote use of improved processing and drying technologies c) assess the quality of cassava chips and d) develop better marketing strategies for cassava chips. The technology was introduced in a participatory manner through mobilization, sensitization, trainings, quality assessment, collective marketing, monitoring and evaluation. As a result, farmers got to know the potential benefits of cassava chips usage in animal feeds. The introduction of the improved drying facilities enabled farmers reduce drying time from 7-10 days as reported in traditional set-up to 1-2 days. The moisture content of the chips (10-12%) processed using the new technology was significantly (P<0.05) lower than that of traditionally processed cassava chips (14-18%). The aflatoxin contamination of well stored processed chips was significantly (p<0.05) lower (>1ppm) than those traditionally processed (15ppm). Cyanide levels in traditionally processed chips (17-35ppm) was significantly (p<0.05) higher compared to chips obtained from processed chips and well stored (1-6ppm). Costbenefit analysis showed that the average cost of producing 1kg of high quality cassava chips was 175/=. The farm gate price of 200/= per 1kg of dried chips offered by the feed miller was found to give a profit of 14% to farmers. Collective marketing through a centralised store has enabled farmers to have stronger bargaining power and bulk selling (>5 tonnes). Due to anticipated income generation from improved processing, acreage under cassava production in the project area increased by over 50%. However, though farmers embraced the improved technology, there still exist some hurdles that are discussed in this paper. The lessons learned from the study will help to improve further out scaling of production and utilisation of cassava technologies in the region.